Potential Test of Trichoderma harzianum and Trichoderma viridae Fungi as Agents for Degrading Fungicide Residues with Active Ingredient Mancozeb In Vitro - Marsya, Tia Indi; Abadi, Abdul Latief (University of Brawijaya, 2024)
This study investigated the potential of the fungi Trichoderma viridae and Trichoderma harzianum in degrading the fungicide mancozeb. The research was conducted from May to October 2021 at the Plant Diseases Laboratory and Toxicology Laboratory, Department of Pests and Plant Diseases, Faculty of Agriculture, Universitas Brawijaya. The study comprised three stages. The first stage involved a preliminary test to assess the ability of T. viridae and T. harzianum to grow in media containing mancozeb-based fungicides. The second stage focused on evaluating the degradation of mancozeb using a bioassay, with the primary observation parameter being the biomass of T. viridae and T. harzianum. In the third stage, the mancozeb degradation process was assessed in vitro, with the observation parameters including the diameter of the pathogenic fungus Fusarium sp. and the percentage change in its diameter. Results demonstrated that T. viridae and T. harzianum could grow in media contaminated with mancozeb up to a concentration of 2 grams per liter. Furthermore, both fungi showed potential in degrading mancozeb, as evidenced by the increased growth of Fusarium sp. in treated media. It indicates that the application of T. viridae and T. harzianum reduces the toxicity of mancozeb. A t-test revealed that while there were differences between T. viridae and T. harzianum in their ability to degrade mancozeb, these differences were not statistically significant.